2021
DOI: 10.1182/blood-2021-146283
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Outpatient CAR T Cell Therapy: Experience of a Single Institution

Abstract: Background Chimeric Antigen Receptor (CAR) T cell therapy has emerged as a promising therapeutic option for relapsed/refractory non-Hodgkin lymphoma. However, access to CAR T cell therapy remains limited as CAR T cells are routinely administered in the hospital setting. Hence, there's a growing interest in standardizing outpatient administration of CAR T cells to increase patient access and minimize costs. Here, we describe our institution's experience with outpatient administration of CAR T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Nine of the shortlisted studies reported efficacy outcomes including response rates and survival outcomes [36,37,39,42,47,55,57,60,63,67]. Only one clinical trial reported QoL in the patient groups of interest [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine of the shortlisted studies reported efficacy outcomes including response rates and survival outcomes [36,37,39,42,47,55,57,60,63,67]. Only one clinical trial reported QoL in the patient groups of interest [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies reported costs/reimbursement amounts associated with the administration of CAR-T in both settings [26,41,52,53,62,65,67]. Ten studies reported data on HCRU [26,37,39,41,[52][53][54]62,67,68] in both settings while a further seven studies reported HCRU among patients who received CAR-T only in the outpatient setting [26,37,39,41,46,[52][53][54][55]57,59,60,[62][63][64]67,68]. The distribution of age, sex, performance status, number of prior treatment lines, and other patient characteristics varied across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations